2018
DOI: 10.1140/epjds/s13688-018-0155-7
|View full text |Cite
|
Sign up to set email alerts
|

The interhospital transfer network for very low birth weight infants in the United States

Abstract: Very low birth weight (VLBW) infants require specialized care in neonatal intensive care units. In the United States (U.S.), such infants frequently are transferred between hospitals. Although these neonatal transfer networks are important, both economically and for infant morbidity and mortality, the national level pattern of neonatal transfers is largely unknown. Using data from Vermont Oxford Network on 44,753 births, 2122 hospitals, and 9722 interhospital infant transfers from 2015, we performed the larges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The proposed surveillance scheme exploits the structure of the hospital network, showing the added value of regarding hospitals as interconnected by shared patients instead of completely independent and isolated entities[812]. Furthermore, the proposed surveillance scheme will likely work in other health care systems in other countries with similar hospital networks consisting of regional groups with large (teaching) hospitals acting as highly connected hubs, such as USA, Netherlands and France [810,1315]. Although the ideal reporting threshold, as well as the required reporting set size would need to be determined on a per country basis, the general principal still applies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed surveillance scheme exploits the structure of the hospital network, showing the added value of regarding hospitals as interconnected by shared patients instead of completely independent and isolated entities[812]. Furthermore, the proposed surveillance scheme will likely work in other health care systems in other countries with similar hospital networks consisting of regional groups with large (teaching) hospitals acting as highly connected hubs, such as USA, Netherlands and France [810,1315]. Although the ideal reporting threshold, as well as the required reporting set size would need to be determined on a per country basis, the general principal still applies.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the hospital network formed by shared patients on the spread of hospital-associated pathogens has also been used to design early warning systems[16,17] or inform the distribution of resources for IPC[18], often reiterating the importance of centrally located hospitals. Previous studies have shown that patient sharing between hospitals significantly correlate with rates of Carbapenemase-Producing Enterobacteriaceae (CPE)[19], MRSA[20] or Clostridium difficile[15,16]. We present a novel viewpoint on using these hospital networks, by considering the interests of hospitals to report cases, thus actively using the shared patients to combat the spread of these pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of these networks can be directly observed through contractual relationships between initial and receiving hospitals or inferred through empirical data on transfers, such as using administrative data 75,76 . Whereas studies have used network analysis techniques to measure and visualize the structure of provider networks, 77–80 relatively few studies have explicitly examined the structure of transfer networks in the United States 77,79–85 . International research on hospital transfer networks 76,86–89 is outside the scope of this paper because of differences in the environments.…”
Section: Structure Of Transfer Networkmentioning
confidence: 99%
“…For instance, 91% of neonatal transports remain within the perinatal referral regions defined by state of California 85 . However, these policies may be limited for patients with specialized needs; state‐level policies may have less of an influence on when very low birth weight infants are transferred 84 …”
Section: Regulatory Environmentmentioning
confidence: 99%
“…The large number of cases in the databases support research on outcomes in specific populations, such as infants with necrotizing enterocolitis (17,18,(60)(61)(62)(63), gastroschisis (64,65), and hypoplastic left heart syndrome (66). Topics in health services research and newborn care include neonatal care utilization in the United States (16,67) and internationally (68), nurse staffing (69)(70)(71)(72), and disparities in care (73)(74)(75)(76).…”
Section: Observational Researchmentioning
confidence: 99%